Resisting the Cultural "Steamroller": Susan Wheeler's Source Codes. - Keller, Lynn (American Literature, 2007)
The essay focuses on the nature of modern avant-garde poetry and the danger of limitation in excessive categorization and critique of innovation. The poetry of Susan Wheeler is highlighted, particularly her generic eclecticism and innovative use of computer language in her collection "Source Codes." Extensive criticism is offered for "Source Codes" along with commentary on her artistic aesthetic progressiveness.